Introduction : children and knowledge in India - Bowen, Zazie (2020)
In contemporary postcolonial India, states, ethnic groups, elites and marginalized people are rearticulating identities in relation to transnational forces. Neoliberal capital and globalization have produced new forms of the ‘politics of culture’1 including: redefinitions of ethnic identities in the context of late capitalism; changing politics around caste; the increasing prominence of Hindu nationalism; and digital media producing new youth identities. To understand these complex social changes, and their historical trajectories, an understanding of the experiences and perspectives of young people is crucial. The articles collected in this special issue are focused on children’s lives in historical and contemporary India, but were informed and enriched by broader discussions about childhood across the South Asian region at an interdisciplinary conference held at The Australian National University in 2013.